2019
DOI: 10.31258/jes.3.3.p.303-317
|View full text |Cite
|
Sign up to set email alerts
|

Reading Experiences on Exploring Personal Reading Histories of English Study Program Learners of University of Riau

Abstract: Learners have different historical reading experiences which can be analyzed from any perspectives. This study aimed to explore “the reading experiences of two successful English study program learners of the Faculty of Teacher Training and Education University of Riau in Extensive Reading course based on Exploring Personal Reading Histories”. The suitable design in answering the research question of this study is a Case Study of the two successful learners in Extensive Reading course. Based on the result of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As Delfi et al (2019) and Spiro (2014) have observed, reading histories allow the participants to share personal experiences that have helped to shape their everyday lives. In answer to the question regarding who influenced participants’ readings of comics, the findings of this research support the literature which agrees that maintaining friendships (Graff, 2009/2010; Moje et al, 2008; Moss, 1993) and the desire to be considered to be a good reader (Merga, 2017; Moss, 1993) are reasons why friends, peers and teachers may have played important roles in the participants’ comics reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Delfi et al (2019) and Spiro (2014) have observed, reading histories allow the participants to share personal experiences that have helped to shape their everyday lives. In answer to the question regarding who influenced participants’ readings of comics, the findings of this research support the literature which agrees that maintaining friendships (Graff, 2009/2010; Moje et al, 2008; Moss, 1993) and the desire to be considered to be a good reader (Merga, 2017; Moss, 1993) are reasons why friends, peers and teachers may have played important roles in the participants’ comics reading.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring reading histories allows researchers and participants to learn about past reading experiences in such a way that time and space allow for deeper introspection into those experiences. Delfi et al (2019: 304) described that asking their college students to explore their personal reading histories for class, “facilitates the learners to recall their reading experiences. It means that they should not think what they are going to tell but they just recall the experiences dealing with reading.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Delfi, et al (2019) also focused on readers' personal reading histories with their college students, but more on the participants' visceral responses to those experiences, considering that those experiences "involve them personally and holistically" (304) and thus their intuitive responses possibly provided greater depth than if they had given planned responses. As Moss (1993) identified in her seminal work with British girls, romance novel reading reflected some of the same types of educational concerns about comics addressed in this paper.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They focus more on speaking skill, not other skills. Delfi (2019) This practice has again indicated that English speaking proficiency is often considered as a special language skill. The learners can evaluate their reading experiences, habits, and attitude in the first, second and the foreign language.…”
Section: Introductionmentioning
confidence: 99%